Book review: Standing Items: critical pedagogies in South African art, design and architecture, edited by Brenden Gray, Shashi Cullinan Cook, Tariq Toffa and Amie Soudien - Bridget Horner (University of Johannesburg, 2020)
In this review of Standing Items: critical pedagogies in South African art, design and architecture, edited by Brenden Gray, Shashi Cullinan Cook, Tariq Toffa and Amie Soudien, book reviewer Bridget Horner observes that for the scholarship of teaching and learning this book could serve as a source of possible teaching methods within the arts; however, this would negate policymakers, management of institutions, educators, discipline professionals and artists from viewing this bookâ€™s real potential, which is identifying and explaining the challenges faced within higher education, as well as opportunities for change â€" through critical pedagogyâ€"  in a country that still holds unaddressed â€˜standing itemsâ€™ related to its colonial and apartheid past within the present neoliberal agenda.   Keywords: Critical pedagogies, South Africa, Book review, Art design and architecture How to cite this article: Horner, B. 2020. Book review: Standing Items: critical pedagogies in South African art, design and architecture, edited by Brenden Gray, Shashi Cullinan Cook, Tariq Toffa and Amie Soudien. Scholarship of Teaching and Learning in the South. 4(2): 239-243. https://doi.org/10.36615/sotls.v4i2.151. This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/